2011
DOI: 10.1242/jeb.053926
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic discrimination of wakes caused by objects of different size or shape in a harbour seal (Phoca vitulina)

Abstract: SUMMARYHarbour seals can use their mystacial vibrissae to detect and track hydrodynamic wakes. We investigated the ability of a harbour seal to discriminate objects of different size or shape by their hydrodynamic signature and used particle image velocimetry to identify the hydrodynamic parameters that a seal may be using to do so. Hydrodynamic trails were generated by different sized or shaped paddles that were moved in the calm water of an experimental box to produce a characteristic signal. In a twoalterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 50 publications
1
61
1
Order By: Relevance
“…Pinnipeds use their vibrissae for the tactile discrimination of surfaces (Dehnhardt, 1994;Dehnhardt and Kaminski, 1995;Grant et al, 2013) and the detection and following of underwater wakes (Dehnhardt et al, 2001;Gläser et al, 2011). Although behavioral and histological evidence suggests that the vibrissal system in pinnipeds is adapted to extract complex tactile information from the environment (Dehnhardt et al, 2014(Dehnhardt et al, , 1998(Dehnhardt et al, , 2001Dehnhardt and Kaminski, 1995;Hanke et al, 2012;Wieskotten et al, 2010Wieskotten et al, , 2011, the sensitivity of this sensory modality is not fully understood. A few studies have utilized different methods to directly measure the tactile sensitivity of seals to a range of stimulus frequencies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pinnipeds use their vibrissae for the tactile discrimination of surfaces (Dehnhardt, 1994;Dehnhardt and Kaminski, 1995;Grant et al, 2013) and the detection and following of underwater wakes (Dehnhardt et al, 2001;Gläser et al, 2011). Although behavioral and histological evidence suggests that the vibrissal system in pinnipeds is adapted to extract complex tactile information from the environment (Dehnhardt et al, 2014(Dehnhardt et al, , 1998(Dehnhardt et al, , 2001Dehnhardt and Kaminski, 1995;Hanke et al, 2012;Wieskotten et al, 2010Wieskotten et al, , 2011, the sensitivity of this sensory modality is not fully understood. A few studies have utilized different methods to directly measure the tactile sensitivity of seals to a range of stimulus frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the sensitivity thresholds overall were elevated relative to what would be expected from an animal that is highly reliant on this mechanoreceptive system for prey detection. Considering the behavioral abilities of these animals to track wakes and determine hydrodynamic features (Dehnhardt et al, 2001;Wieskotten et al, 2010Wieskotten et al, , 2011, the seal's vibrissal system would need to be highly sensitive. Although there are limited psychophysical data to allow for comparison with other whiskered mammals, it has been demonstrated that the rat (a known vibrissal specialist) can detect stimulus movements as slight as 11 µm at 80 Hz with their vibrissae (Adibi and Arabzadeh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A submarine was com- Figure 1-21: Different shapes that a seal was trained to distinguish based solely on the wake left while they were held fixed and towed. Figure from [140].…”
Section: Impact Of Glide Phasesmentioning
confidence: 99%
“…Object Size and Shape [140] showed the seals' ability to distinguish certain sizes and shapes of objects based on their hydrodynamic signature. Chemically inert paddles of different shapes ( Figure 1-21) and sizes were towed in front of a blindfolded seal.…”
Section: Impact Of Glide Phasesmentioning
confidence: 99%
“…Harbour seals (Phoca vitulina) are able to detect and follow such hydrodynamic trails (Dehnhardt et al 2001). Subsequent studies showed that they can even further analyse the structure of water disturbances (Wieskotten et al 2010(Wieskotten et al , 2011. The detection and analysis of water movements by pinnipeds is described and reviewed by W. Hanke et al in this issue.…”
mentioning
confidence: 99%